2021
DOI: 10.1097/01.aoa.0000796196.30132.44
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Preoperative Rectal Misoprostol and Intraoperative Intrauterine Administration in the Reduction of Blood Loss During and After Cesarean Delivery: A Randomized Controlled Trial

Abstract: patients who were confirmed with COVID-19 postoperatively (20.4%) compared with preoperatively (9.1%). Care and staffing needs differ, so preoperative COVID-19 testing and diagnoses can be helpful to ensure needs are met before complications arise. Strategies can be implemented to address more emergent surgeries where prior testing is not feasible. When making discussions, the mother, neonate, and HCWs should be considered to minimize risk and improve safety for all involved. Future research and studies should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
0
1
Order By: Relevance
“…The weight difference of soaked towels in both groups was comparable. Our findings are similar to but lower weight difference of soaked towels in the study [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The weight difference of soaked towels in both groups was comparable. Our findings are similar to but lower weight difference of soaked towels in the study [21].…”
Section: Discussionsupporting
confidence: 90%
“…The most common indication for LSCS was fetal distress followed by cord prolapse in both groups. The pre-operative hemoglobin was comparable between the two groups while the post-operative hemoglobin in Group I and Group II was found to be highly significant (p value < 0.01) which were comparable with [16,20,21] showed that the mean drop in hemoglobin was not significantly different between the two groups which is contrary to our study [22].…”
Section: Discussioncontrasting
confidence: 74%
“…Based on the current study, participants who were administered with rectal Misoprostol preoperatively had lower Apgar scores at 1 & 5 min compared to those treated with intrauterine Misoprostol. The present finding agrees with the study of El-Sherbini et al [16] , who observed that the combined usage of Misoprostol with oxytocin intrauterine or rectally lowers operational blood loss and PPH as effectively as the use of either agent alone. Misoprostol has no side effects other than shivering, fever, and nausea, regardless of whether a rectalintrauterine route of administration is used.…”
Section: Majed Et Alsupporting
confidence: 93%